2021
DOI: 10.1186/s13023-021-01759-8
|View full text |Cite
|
Sign up to set email alerts
|

Extending the phenotypic spectrum of PRPF8, PRPH2, RP1 and RPGR, and the genotypic spectrum of early-onset severe retinal dystrophy

Abstract: Purpose To present the detailed retinal phenotype of patients with Leber Congenital Amaurosis/Early-Onset Severe Retinal Dystrophy (LCA/EOSRD) caused by sequence variants in four genes, either not (n = 1) or very rarely (n = 3) previously associated with the disease. Methods Retrospective case series of LCA/EOSRD from four pedigrees. Chart review of clinical notes, multimodal retinal imaging, electrophysiology, and molecular genetic testing at a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…73 It can cause adRP and autosomal recessive (ar) RP, early onset severe retinal dystrophy (EOSRD), MD and CORD. 74,75 Genotype-phenotype correlations have been described, where truncations affecting the middle portion of the gene were associated with adRP (Arg677Ter being the third most common adRP variant described), while those in the N-and C-terminals caused arRP. 76,77 adRP1 has a similar phenotype to RHO-RP, and also often presents with wide phenotypic variability, with asymptomatic carriers described.…”
Section: Rp1mentioning
confidence: 99%
See 1 more Smart Citation
“…73 It can cause adRP and autosomal recessive (ar) RP, early onset severe retinal dystrophy (EOSRD), MD and CORD. 74,75 Genotype-phenotype correlations have been described, where truncations affecting the middle portion of the gene were associated with adRP (Arg677Ter being the third most common adRP variant described), while those in the N-and C-terminals caused arRP. 76,77 adRP1 has a similar phenotype to RHO-RP, and also often presents with wide phenotypic variability, with asymptomatic carriers described.…”
Section: Rp1mentioning
confidence: 99%
“…PRPH2 has great phenotypic variability, being associated with adRP, MD, pattern dystrophy, central areolar choroidal dystrophy, and EOSRD. 75,[79][80][81] Despite the noteworthy inter-and intrafamilial variation and even incomplete penetrance, genotype-phenotype correlations have been developed, where Arg142Trp and Arg172Trp generally result in MD, and variants between Pro210 and Pro216, in adRP. 82 Patients with pattern dystrophy tend to remain asymptomatic until the fifth decade of life, while the majority of individuals with adRP have symptoms between the third and fifth decade.…”
Section: Prph2mentioning
confidence: 99%
“…An alternative to the latest MP devices may be the dark-adapted chromatic Medmont M700 perimeter (Medmont International Pty Ltd), which has been designed to probe different photoreceptor mechanisms 24 , 25 but requires further investigation. Further exploration of retinal function in affected females with RPGR retinopathy will be of value 26 as well as correlation of MP with advanced cellular imaging techniques. 27 , 28…”
Section: Discussionmentioning
confidence: 99%
“…RP1 is related to both ADRP (mostly) and ARRP (rarely). [ 59 60 ] RP1 -induced ARRP has more severe disease symptoms than RP1 -induced ADRP. Animal studies have shown that ADRP causing RP1 variations works in a dominant-negative way.…”
Section: Retinitis Pigmentosa1 Genementioning
confidence: 99%
“…[ 55 ] Amino acid residues between 500 and 1053 (in exon 4) act as a variational hotspot for ADRP. [ 60 ] RP–causing truncating variations in the RP1 gene have been divided into four classes. Variations of class I occupy the 2 nd and 3 rd exons and work in a loss-of-function manner.…”
Section: Retinitis Pigmentosa1 Genementioning
confidence: 99%